Zinc and copper in multiple sclerosis. Issue 8 (August 1982) - Palm, R; Hallmans, G
Abstract : The serum concentrations of zinc and copper were measured in 50 patients with multiple sclerosis. Lower serum zinc levels were found compared to age- and sex-matched controls. In younger patients low serum copper concentrations were noted. Zinc concentrations in CSF were unchanged. The possibility that malabsorption of the metals causes the low serum concentrations is discussed.